Perceived Role of Marketing Communication Strategies on Students’ Enrollment in Private Secondary Schools in Mbale Municipality, Mbale District - Mukwana, Siragi; Matovu, Musa (Journal of Education and Practice, 2018)
secondary schools in Mbale municipality, Mbale district. The hypotheses of the study were; (a) external marketing communication strategies have no statistically significant effect on students’ enrollment in private secondary schools in Mbale municipality, (b) internal marketing communication strategies have no statistically significant effect on students’ enrollment in private secondary schools in Mbale municipality, and (c) relationship marketing communication strategies have no statistically significant effect on students’ enrollment in private secondary schools in Mbale municipality. A correlation research design was adopted for the study, with a population of 290 from which a sample of 165 was selected. A closed ended questionnaire was used for data collection, with both descriptive statistics and inferential used for data analyses. The study discovered significant effects between external marketing communication strategies on students’ enrollment (r = .490, N= 158, p<.05, β =.490), internal marketing communication strategies on students’ enrollment (r = .493, N =158, p< .05, β =.493), and relationship marketing communication strategies on students’ enrollment (r = .594, N =158, p<.05, β =.594). This implies that a unit change in external, internal and relationship marketing communication strategies leads to a 49.0%; 49.3% and 59.4% change in students’ enrollment respectively. The study concludes that external, internal and relationship marketing communication strategies have a statistically significant effect on students’ enrollment in private secondary schools in Mbale Municipality. Due to a higher effect relationship marketing communication strategies should be given priority when undertaking marketing in private secondary schools in Mbale Municipality, Mbale District.
Keywords: Marketing communication strategies; Students’ enrollment; Private secondary schools; Mbale municipality